Human Rights and the role of courts in Thailand - Tamisanont, Choocheewan (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The purpose of the article is to analyse the subject of the problems involved in protecting human rights in Thailand and the role of the courts according to the Thai Constitution. The author discusses four selected issues of human rights protection in Thailand: the citizens’ insufficient awareness of human rights, the ineffectiveness of law enforcement,the possible conflicts linked to traditional beliefs and the problems of applying double standards. The article also presents the structure and the function of the Constitutional Court, the Court of Justice and the Administrative Court of Thailand. Throughout the paper the author seeks to prove that the Constitution of the Kingdom of Thailand honours and protects human rights.